Legal Protection of Trademark Holders Against Imported Goods: A Contextual Framework under Islamic Economic Law - Elfi Haris; OK Saidin; Ningrum Natasya Sirait; Maria Kaban; Ruetaitip Chansrakaeo (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
The increasing influx of imported goods in Indonesia has intensified market competition and created complex challenges in protecting the rights of local trademark holders. Weak enforcement mechanisms and limited public awareness have facilitated imitation and unfair competition, threatening economic sustainability and consumer confidence. This study examines the adequacy of Indonesia’s trademark protection and reinterprets it through the ethical and normative framework of Islamic economic law. Using a normative juridical approach with statutory, conceptual, and comparative methods, the research analyzes Law No. 20 of 2016 on Trademarks and Geographical Indications alongside Islamic legal principles such as maqāṣid al-sharī‘ah (objectives of Islamic law), hifẓ al-māl (protection of wealth), and maṣlaḥah ‘āmmah (public interest). This analytical synthesis evaluates the harmony between positive law and Islamic ethics in regulating fair competition. The findings reveal that Indonesia’s legal framework provides sufficient formal protection but remains ineffective due to weak implementation, inadequate sanctions, and the limited capacity of small and medium enterprises. Conversely, Islamic economic principles emphasize moral accountability, fairness, and transparency as essential to market justice. Integrating these ethical values into trademark regulation would not only strengthen compliance but also foster socially responsible trade practices. This study contributes to contextualized Islamic law by proposing an integrated model that harmonizes intellectual property protection with Islamic moral economy. It advances theoretical understanding by linking fiqh mu‘āmalah with modern IP law and offers policy recommendations for promoting ethical branding, fair competition, and sustainable economic protection for Indonesian industries